ANALISIS SPASIAL SEBARAN IPAL RS DI WILAYAH KOTA KENDARI BERDASARKAN EFEKTIVITAS PENGELOLAANNYA - Desy Rahmawati; M. Tufaila Hemon; Nani Yuniar (Universitas Halu Oleo, 2019)
This study aims to determine the quality of hospital wastewater that has gone through processing, toknow the effectiveness of Hospital Wastewater Treatment Plants in Kendari City, to know the distribution ofHospital Wastewater Treatment Plants based on the quality of their wastewater and develop managementstrategies. This type of research is qualitative descriptive with a survey approach. In this study, sampleswere taken in the inlet pipe section and the hospital wastewater treatment plant with BOD5, COD and TotalColiform test parameters. The results showed that based on the COD and BOD5 parameters of 8 (eight)hospitals that have only 1 (one) hospital wastewater treatment plant whose test results exceeded the qualitystandard based on KepmenLH no.05 of 2014. Total Coliform parameters were 8 (eight ) hospitals that havea Waste Water Treatment Plant have 2 (two) hospitals whose test results exceed the quality standards basedon KepmenLH no.05 of 2014. Effectiveness of hospital wastewater treatment plants based on BOD5 testparameters which have effectiveness between > 67-100% there are 6 (six) hospitals, the effectivenessbetween > 34 - 67% there is 1 (one) hospital and the effectiveness between 0 - 34% there is 1 ( one) hospital.Effectiveness based on COD parameters, effectiveness between > 67-100% there are 5 (five) hospitals,effectiveness between > 34 - 67% there is 1 (one) hospital and effectiveness between 0 - 34% there are 2(two) hospitals. Effectiveness based on total coliform parameters, effectiveness between > 67-100% thereare 3 (three) hospitals, effectiveness between > 34-67% there are 3 (three) hospitals and effectivenessbetween 0 - 34% there are 2 (two) hospitals. 2 (two) hospitals cannot evaluate their effectiveness becauseIPAL is not functioning / not functioning. Strategies that need to be carried out include managementstrategies, technical strategies and monitoring strategiesKeywords: Spatial Analysis, Management Effectiveness of Hospital Waste Water Treatment Plants